2010
DOI: 10.1128/aem.02373-09
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Environmental Stress on Stability of Tandem Repeats in Escherichia coli O157:H7

Abstract: Multilocus variable-number tandem-repeat analysis (MLVA) is used for source tracking Escherichia coli O157:H7 in agricultural environments. Tandem repeats were stable after limited replication but changed after exposure to irradiation, elevated temperatures, and starvation conditions. The pO157 plasmid was frequently lost under these stress conditions. Environmental stresses may increase phylogenetic diversity as measured by MLVA.Escherichia coli O157:H7 is a pathogen causing serious disease that survives in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
26
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 33 publications
3
26
0
Order By: Relevance
“…The generated variations in one or more VNTRs might cause the MLVA results for identical clones to appear different (19). In addition, environmental stress can affect the stability of tandem repeats (31). Most of the mutations in VNTR units were shown to be single-repeat differ- ences (32), but multiple-repeat mutations also occur.…”
Section: Discussionmentioning
confidence: 99%
“…The generated variations in one or more VNTRs might cause the MLVA results for identical clones to appear different (19). In addition, environmental stress can affect the stability of tandem repeats (31). Most of the mutations in VNTR units were shown to be single-repeat differ- ences (32), but multiple-repeat mutations also occur.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study has demonstrated that ultrasound, especially at 60 W for 3 min, significantly enhanced membrane permeability, which subsequently promoted the growth of lactobacilli and bifidobacteria and bioconversion of isoflavones in mannitolesoymilk (Yeo & Liong, 2011). Past study has demonstrated that bacterial cells expose to stressful condition may possibly exhibit heritable changes and thus the altered characteristics would also be prevalent in subsequent passages of cells (Cooley, Carychao, Nguyen, Whitehand, & Mandrell, 2010). However, the inheritance of beneficial effect by subsequent passages of ultrasound-treated cells remains unclear.…”
Section: Introductionmentioning
confidence: 96%
“…However, because MLVA relies on genetic loci having intrinsically high mutation rates [9], VNTR loci can be affected by treatments such as environmental stress and serial passaging, leading to alteration in the MLVA fingerprints of organisms of interest [9,13,14]. For this reason, a better understanding of the stability and mutational rates of VNTR loci is needed to permit the interpretation of MLVA results in forensic investigations [15,7].…”
Section: Introductionmentioning
confidence: 99%